Ethnopharmacological Insights into Asteraceae: Traditional Medicine and Therapeutic Potential in the Gayo Highlands, Bener Meriah Regency - Puspa, Vivera Ruselli; Zumaidar; Nurdin; Fitmawati; Fathiya, Nir (Universitas Islam Negeri Ar-Raniry, 2026)
The Gayo Highlands communities use Asteraceae species in traditional medicine to treat various ailments. This study aimed to document the ethnopharmacological use of Asteraceae and assess community knowledge regarding their medicinal applications. Data were collected from 48 respondents across eight sub-districts using purposive sampling and structured questionnaires. The study identified 10 Asteraceae species used to treat 10 diseases, including diabetes mellitus (DM), cancer, hypertension, liver disorders, common cold, bloating, cough, fever, toothache, and skin itching. Leaves were the most frequently used plant organ (95.96%), mainly from wild plants growing near home yards or abandoned land. Approximately 81.25% of respondents reported using Asteraceae to manage DM. Standard preparation methods included boiling and pounding, with the leaves of Erigeron sumatrensis Retz being the most widely recognized and utilized for the treatment of DM and cancer. The community’s preference for these plants is attributed to their availability, perceived safety, and efficacy. This study highlights the significant ethnopharmacological potential of Asteraceae in the Gayo Highlands and provides a basis for further pharmacological investigations, particularly on E. sumatrensis. Keyword: Asteraceae; traditional medicine; ethnopharmacology; Gayo Highlands; Erigeron sumatrensis